Complexity, Objectivity, and Shifting Roles: Environmental Correspondents March to a Changing Beat. (21st October 2021) - Robbins, David; Wheatley, Dawn
ABSTRACT: Environmental journalists have been at the forefront of news industry changes. Over the past 30 years, they have had to deal with a range of challenges, including increased complexity, greater reliance on data, exposure to online negativity, and co-option into polarised political debates. At the same time, they have been among the most vulnerable to newsroom cutbacks. This exploratory study examines the extent to which environmental journalists can be considered emblematic of challenges facing beat journalism in general. Drawing on rare, on-the-record interviews with environmental reporters in the US, UK, and Ireland, the study finds that, based on environmental journalists' experiences, specialised environmental beats are becoming the preserve of larger media organisations with dedicated audiences, while at smaller news outlets, specialist reporters have taken on two or more beats, thereby diluting coverage of specific areas overall. Environmental journalists have also had to reconsider traditional roles, such as the conduit function, and long-standing norms, such as objectivity and impartiality. These trends may come to be replicated across other beats as journalists begin to report from a social justice standpoint, or rely more on science and data, as has happened during Covid-19 coverage.